Oro - BINDI, LUCA (Firenze University Press, 2007)
The word "gold" has influenced the imaginations of various populations over the centuries and the search for gold has been an extremely fascinating event to a multitude of societies in the past. In this publication, which is part of the "Le Perline del Museo" series of the Natural History Museum of the University of Florence, the concept of "gold" is explored from several points of view. The book is divided into 11 chapters dealing with gold from various points of view: its chemical-physical properties, how and where it can be found in nature, the mineralogy of gold, the processes to extract it, what can be done with gold and gold over the centuries, up to a brief description of the California "gold rush" of the late nineteenth century. The publication is enriched with beautiful images of gold in all its forms. For the realisation of the publication, the author collaborated with the American Museum of Natural History (New York, USA), the Museum of the City of San Francisco (San Francisco, USA) and the Metropolitan Museum of Art (New York, USA).